'Take care of your soil' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
video, entitled 'Lukautim Graun Bilong Yu' (Take Care of your Soil), is a 22 minute documentary